Oral-Based Christian-Marapu Interreligious Engagement: Manawara as a Shared Virtue for Common Liberation - Krisharyanto Umbu Deta (Jurnal Dialog, 2021)
This has been prevalent that the discourse of interreligious dialogue has been overwhelmingly dominated by the elites in the formal spheres. It even seems to be the only standard to examine the issues of interreligious relations, without taking into account the diverse modes of everyday engagements among the people. This then raises the recognition that there is actually no single pattern for interreligious engagement since it would be always contextual according to its distinctive context. It therefore implies the need to learn more from the localities to develop more contextual interreligious engagement. In this regard, this work will examine the interreligious engagement of Christianity and Marapu indigenous religion in Sumba. The data used in this work are based on the field research conducted in 2019 in Southwest Sumba. Observation and in depth interview with a number of Sumbanese Christians and Marapu are also conducted. The research finds that manawara (the teaching of love; compassion) as the potential basis for developing social engagement. The term manawara is used by Marapu people in their teaching, but since the term is a Sumbanese language, the Sumbanese Christians also translate their prominent teaching of love with that term. Manawara is then both scriptural-based for Christians, and oral-based for Marapu people. Using Lattu’s oral-based interreligious engagement and Knitter’s socially engaged dialogue as the theoretical frameworks, this work argues that manawara as a shared virtue is very potential to be developed, in realizing common liberation of the Sumbanese through mutual action. Keywords: interreligious engagement, manawara, orality, sumbanese christian, marapu indigenous rel Wacana dialog antaragama selama ini telah didominasi sedemikian rupa oleh para elit dalam ruang-ruang formal. Hal itu bahkan menjadi seolah satu-satunya ukuran untuk membahas isu-isu hubungan antaragama, tanpa memperhitungkan keberagaman bentuk keterlibatan sehari-hari yang dihidupi secara nyata oleh orang-orang beragama yang merupakan subjek utama dalam topik tersebut. Dari sinilah kemudian muncul kesadaran bahwa sebenarnya tidak ada satu pola tertentu untuk keterlibatan antaragama karena ia akan selalu tergantung pada konteksnya yang unik. Hal ini menunjukkan bahwa penting untuk lebih banyak belajar dari lokalitas-lokalitas yang ada demi mengembangkan keterlibatan antaragama yang lebih kontekstual. Untuk itu, tulisan ini akan membahas keterlibatan antaragama Kristen dan Marapu di Sumba. Data yang digunakan dalam studi ini diperoleh dari sebuah penelitian lapangan pada tahun 2019 di Sumba Barat Daya yang dilakukan melalui observasi dan wawancara mendalam dengan sejumlah orang Sumba Kristen dan Marapu. Penelitian tersebut menemukan manawara (ajaran tentang kasih) sebagai basis potensial untuk mengembangkan keterlibatan yang ada. Istilah manawara digunakan oleh orang Marapu dalam ajaran mereka, namun karena istilah tersebut adalah sebuah kata dalam Bahasa Sumba, orang Sumba Kristen juga menerjemahkan ajaran kasih mereka dengan istilah manawara tersebut. Dengan demikian, manawara menjadi suatu ajaran yang basisnya skriptural, bagi orang Kristen, dan oral, bagi orang Marapu. Dengan menggunakan keterlibatan antaragama berbasis oral dari Lattu dan socially engaged dialogue dari Knitter sebagai kerangka teori, studi ini berargumen bahwa manawara sebagai sebuah kebajikan bersama sangatlah potensial untuk dikembangkan, dalam merealisasikan pembebasan bersama orang Sumba melalui aksi bersama. Kata Kunci: keterlibatan antaragama, manawara, kelisanan, orang Kristen Sumba, agama Marapu